Synthesis of single phase Ti4+ substituted Trirutile CoNb2O6 Ceramic: evolution of Relaxor type ferroelectricity and high k dielectricity - Singh N.; Kumar K.; Singh P. (My University, 2025)
The dielectric constant of material ultimately decides the level of miniaturization in electronic devices based on capacitive components and the development of wireless communications technologies operating at microwave frequencies. Similar to well-known PZT type high k (dielectric constant) Ferroelectrics, Ti4+ ion doping is tried here in a novel Trirutile CoNb2O6 lattice as smaller Ti4+ can vibrate from its mean position in Trirutile octahedral resulting in the net polarization in the octahedral that can result in high k dielectricity and overall can turn Trirutile into a new family of ferroelectrics. Single phase Ti substituted Trirutile CoNb2O6 ceramic were synthesized for the first time by solid-state ceramic synthesis route and Phase purity and substitution of Ti4+ ions in CoNb2O6 Trirutile lattice was confirmed using Powder x-ray diffraction (XRD), Scanning Electron Microscope(SEM), and Energy Dispersive X-ray analysis (EDX), X-ray Photoelectron Spectroscopy (XPS). Both dielectric constant and dielectric loss were decreasing with increasing frequencies. Ti4+ substitution in the Trirutile CoNb2O6 lattice enhances the dielectric constant of the material. The dielectric constant (ɛr′) for CoNb2O6 was found to be 500, CoNb1.95Ti0.05O6 is 700 and CoNb1.9Ti0.1O6 is 14,000 respectively at 100 Hz frequency at 200 oC and then decreases, it clearly shows the relaxor type behavior. Samples also exhibit ferroelectric behavior with remnant polarization Pr and Vc at 50 Hz frequency equal to 0.05 µC/cm2 and 8e + 03 V/cm for CoNb1.95Ti0.05O6 and 0.05 µC/cm2 and 10e + 03 V/cm for CoNb1.9Ti0.1O6. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.